THE TRANSFORMATION OF THE CULTURE AND LANGUAGE OF INTIMACY - Necef, Mehmet Ümit (Psyke & Logos, 2022)
Immigrants originating from »traditional« societies go through a transformation of culture and language of intimacy in Denmark. Many first and second generation Turkish immigrants either use Danish words or shift totally to Danish when speaking about sexual and intimate matters in Turkish. Turkish males make use of the new possibilities for sexual and intimate gratification with Danish women, while trying to preserve the original ethnic culture, especially in areas pertaining to women’s control over their bodies and sexualities. Research on immigrants should take into account both the willingness and resistance to change among immigrants and avoid cultural patronizing.